First approach to the knowledge of the coral communities of the reef complexes of Serranilla, Bajo Alicia and Bajo Nuevo-Colombia, northern section of the Seaflower Biosphere Reserve, Western Caribbean - Abril-Howard, Alfredo (2012)
Given the difficulty to visit Serranilla, Alice Shoal, and New Shoal, information about their ecosystems is limited and the only data available comes from landings of the industrial fishing fleet. We visited these areas in order to study their reef systems; coral cover was estimated at 26, 14, and 42 stations, respectively. Characterization was made using the ERA method, monitoring 400 m2 per station. Coral cover in New Shoal was 30.2% ± 19.1%, and peripheral reefs showed similar growth to the ones described for other similar oceanic formations in the Archipelago. The lagoon has depths between 6-20 m, where living coral reached up to 70%. In Serranilla, coral cover was low (13.0 ± 6.9%), macroalgae was dominant in most of the stations (43.8% ± 15.7%), and the genus Gorgonia was highly dominant (20.8 ± 15.2%). The highest coral cover was found in the largest fraction of the barrier (NW). The Alice Shoal reef is permanently submerged and is dominantly covered by macroalgae (32.9% ± 17.1%); coral growth (15.7% ± 7.9%) is associated with cracks and elevations of the calcareous matrix. Currently, reef conditions in the Archipelago are similar, although isolation plays a central role in the conservation of New Shoal, where the hard coral cover is the largest in the entire Seaflower Biosphere Reserve.